2012
DOI: 10.1093/toxsci/kfs148
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Induces Hepatic Hypoxia and Increases EndothelialCell Proliferation in Mice, a Process Inhibited by DietaryVitamin E Supplementation

Abstract: The preceding article identified key components of pregabalin's mode of action on nongenotoxic hemangiosarcoma formation in mice, including increased serum bicarbonate leading to decreased respiratory rate, increased blood pH, increased venous oxygen saturation, increased vascular endothelial growth factor and basic fibroblast growth factor expression, increased hepatic vascular endothelial growth factor receptor 2 expression, and increased iron-laden macrophages. Increased platelet count and platelet activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Specifically, pregabalin induces macrophage activation and increased angiogenic growth factors in bone marrow, spleen, and liver tissues, with a high incidence of hemangiosarcomas in the mouse (Criswell et al, 2012a). Pregabalin also increased local tissue hypoxia and endothelial cell proliferation in mouse liver (Criswell et al, 2012b), which are hallmarks of nongenotoxic tumor formation. All of these changes were absent in the rat.…”
Section: Analysis Of P53 and Ras Gene Mutationsmentioning
confidence: 99%
“…Specifically, pregabalin induces macrophage activation and increased angiogenic growth factors in bone marrow, spleen, and liver tissues, with a high incidence of hemangiosarcomas in the mouse (Criswell et al, 2012a). Pregabalin also increased local tissue hypoxia and endothelial cell proliferation in mouse liver (Criswell et al, 2012b), which are hallmarks of nongenotoxic tumor formation. All of these changes were absent in the rat.…”
Section: Analysis Of P53 and Ras Gene Mutationsmentioning
confidence: 99%
“…Administration of pregabalin with alcohol or benzodiazepines may synergistically depress neuronal conduction in the CNS possibly due to the enhancement of GABA mediated actions and inhibition of Ca 2+ mediated glutamate release at synapses [85]. In preclinical studies, pregabalin has been shown to induce bone marrow changes, hepatic hypoxia, endothelial cell proliferation and hemangiosarcoma in mice [86-88]. The combination of hypoxia and sustained increase in endothelial cell proliferation, angiogenic growth factors, dysregulated erythropoiesis, and macrophage activation has been hypo-thesized as the key event for the hemangiosarcoma formation in mice [89].…”
Section: Side Effectsmentioning
confidence: 99%
“…Knowledge of the mechanism of hemangioma induction has increased, and it is now thought that increased bicarbonate, and dysregulated erythropoiesis, macrophage activation, and increased angiogenic growth factors may all be important 91. Pregabalin appears to induce hypoxia and endothelial cell proliferation in a species-specific manner, but these effects can be inhibited by vitamin E, presumably due to its antioxidant and antiangiogenic properties 92. Based on an extensive dataset, a recent review concluded that the findings seen in mice are not relevant to humans at the clinical dose of pregabalin, and that use of pregabalin does not pose an increased risk for hemangiosarcoma in humans 93…”
Section: Tolerability and Safety Of Pregabalinmentioning
confidence: 99%